The Fall of R’Thea: Digital Fiction - Polydorou, Doros (My University, 2023)
This paper outlines the creative process and the immersive approaches undertaken to create the location-based story- telling experience The Fall of R’Thea. The installation revolves around the theme or Artificial Intelligence, digital humans and artificial life and aims to immerse the users into a hybrid environment of a physical and virtual nature. The experience is told through multiple mediums, and the story needs to be carefully pieced together by the audience. As this experience requires participants to engage in various activities, the immersive qualities shift in type and intensity. The authors, through this paper, aim to share the approaches they chose to immerse the participants into their spaces, as well as highlight the challenges and the lessons they learned.
Keywords: Immersive approaches; Story- telling